MANFAAT BASIS DATA DALAM MANAJEMEN PRODUKSI - Anggi Nurafni; Putri Indah Lestari, Adila Khairani, Tony Junior Barus, Nurbaiti (CV. ADIBA AISHA AMIRA, 2023)
The development of information technology at this time is very helpful for every human work. As in the case of data collection, everyone in an institution or company cannot be separated from using a DBMS (Database Management System).The database is an important component in the information system, because it serves as the basis for providing information to its users.The application of the database in an information system is called a database system.This database system (database system) is an information system thatintegrate a collection of data that are interconnected with each otheranother and make it available for a wide variety of applicationswithin an organization.The goal of database design is to define data needed in the system, so that the resulting information can be fulfilled well. Databases that are already included in a storage media are not will never be accessible without the presence of an application software familiar with it, let's say application software base database.